Upaya Meningkatkan Partisipasi dan Hasil Belajar IPS melalui Pendekatan Pembelajaran Kooperatif Model Group Investigation - Nursiah (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2022)
This study aims to determine the extent to which Efforts to Increase Participation and Learning Outcomes in Social Studies Learning through Cooperative Learning Approach Group Study Model (Group Investigation) in Class IX-3 Students of SMP Negeri 1 Taliwang. This research is a classroom action research conducted in two cycles, each cycle has two meetings and an assessment is carried out at the end of each cycle to determine whether there is an increase in student participation in social studies learning and social studies material mastery. The action given is in the form of a group study model as an effort to improve social studies learning and increase participation and social studies learning outcomes, the research was carried out on Class IX-3 students of SMP Negeri 1 Taliwang. The results of data analysis show that learning the group study model can increase student activity. Students dare to ask questions, communicate, answer questions from teachers, friends, or other groups and dare to defend their opinions when discussing. The increase in participation and social studies learning outcomes can be seen from the acquisition of student scores before the action was given, which was an average of 71.25, to 77.14 in the first cycle. The achievement of material mastery before the action was taken was 13 students (46.43%), increased to 20 students (71.42%) in cycle I. In cycle II the average value increased to 84.71 and students who had achieved completeness 28 students (85.71%) in the final test of the cycle the average score of students became 80.93 The Group Study learning model was able to increase student learning participation in class IX- 3 at SMP Negeri 1 Taliwang because learning with the Group Study model can create an active, innovative, creative and fun learning atmosphere